2009
DOI: 10.1037/a0015401
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of response to medication and cognitive therapy in the treatment of moderate to severe depression.

Abstract: A recent randomized controlled trial found nearly equivalent response rates for antidepressant medications and cognitive therapy in a sample of moderate-to-severely depressed outpatients. In this article, we seek to identify the variables that were associated with response across both treatments as well as variables that predicted superior response in one treatment over the other. The sample consisted of 180 depressed outpatients: 60 of whom were randomly assigned to cognitive therapy; 120 were assigned to ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
352
9
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(382 citation statements)
references
References 73 publications
11
352
9
4
Order By: Relevance
“…Partly, these findings have been confirmed by Carter and colleagues who also found that a treatment response to either CBT or IPT is predicted by the perceived logicalness of the therapy (which conforms to the predictive value of the afore mentioned expectation of improvement), recurrent depression, and childhood reasons for the depression [35]. Furthermore, Fournier and colleagues found that older age and chronic depression predict relatively poor outcome following CBT as well as following ADM [36]. Uncontrolled pre-post-studies revealed that being married and displaying a lower initial symptom severity are prognostic of better response to CBT [37][38], however, it is unclear whether this finding is treatment-specific.…”
Section: Some Patient Characteristics With Unclear Status: Prognosticsupporting
confidence: 65%
See 2 more Smart Citations
“…Partly, these findings have been confirmed by Carter and colleagues who also found that a treatment response to either CBT or IPT is predicted by the perceived logicalness of the therapy (which conforms to the predictive value of the afore mentioned expectation of improvement), recurrent depression, and childhood reasons for the depression [35]. Furthermore, Fournier and colleagues found that older age and chronic depression predict relatively poor outcome following CBT as well as following ADM [36]. Uncontrolled pre-post-studies revealed that being married and displaying a lower initial symptom severity are prognostic of better response to CBT [37][38], however, it is unclear whether this finding is treatment-specific.…”
Section: Some Patient Characteristics With Unclear Status: Prognosticsupporting
confidence: 65%
“…Fournier and colleagues found that marriage, unemployment, and having experienced a greater number of recent life events predict superior response to CBT as compared to ADM [36]. Interestingly, in another study Barber and Muenz found that married patients did better with CBT than they did with IPT whereas unmarried patients did better with IPT than with CBT [52].…”
Section: Some Moderating Patient Characteristicsmentioning
confidence: 93%
See 1 more Smart Citation
“…Due to the explorative nature of the prediction analysis, we aimed at generating (instead of testing) hypotheses regarding the associations between potential predictive variables and the clusters. In line with previous work exploring predictors of outcome, potential predictors were classified into different domains and a stepwise procedure was used for each predictor domain (de Kleine, Hendriks, Smits, Broekman, & van Minnen, 2014; Fournier et al, 2009). In step 1, a model including all variables for a given domain was tested.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent findings across studies are required before we can consider moderators as clinically informative and, ideally, the field should aim for meta-analyses of randomised studies using individual patient data to achieve sufficient statistical power. 169 To date, studies reporting moderators of response to CBT in controlled trials have used small sample sizes, randomising fewer than 63 patients per CBT arm, [170][171][172][173][174] or have compared CBT to antidepressant treatment, 172,173 or have focused on adolescent or elderly populations. [175][176][177] With such small sample sizes these studies were almost certainly underpowered, 167 and although understanding which of two treatment options is likely to produce the best outcomes is important, antidepressants and CBT are often prescribed together in practice.…”
Section: Clinical Problemmentioning
confidence: 99%